2014
DOI: 10.1118/1.4863597
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of markerless EPID tracking for tumor position verification in gated radiotherapy

Abstract: In this retrospective analysis of motion data, it is demonstrated that the system is capable of determining tumor positions in the plane perpendicular to the beam direction without the aid of fiducial markers, and may hence be suitable as an online verification tool in RGRT. It may be possible to use the tracking information to enable on-the-fly corrections to intra-/inter-beam variations by adapting the gating window by means of a robotic couch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 47 publications
(87 reference statements)
0
23
0
Order By: Relevance
“…If a tumor happens to be temporarily out of the planned position, the dosimetric differences may be exacerbated compared to treatment using longer beam on times. 6 The feasibility of markerless lung tumor tracking in 2D has been reported by a number of groups using the MV treatment beam [7][8][9][10][11][12] or kV imaging systems. [13][14][15] Using EPID movie-based tumor tracking, Richter et al 7 showed in 40 patients treated using static beams that the difference between automatic and manual tracking was a maximum of 2 mm for 98.3% in the X-direction and 89.4% in the Y -direction.…”
Section: Introductionmentioning
confidence: 99%
“…If a tumor happens to be temporarily out of the planned position, the dosimetric differences may be exacerbated compared to treatment using longer beam on times. 6 The feasibility of markerless lung tumor tracking in 2D has been reported by a number of groups using the MV treatment beam [7][8][9][10][11][12] or kV imaging systems. [13][14][15] Using EPID movie-based tumor tracking, Richter et al 7 showed in 40 patients treated using static beams that the difference between automatic and manual tracking was a maximum of 2 mm for 98.3% in the X-direction and 89.4% in the Y -direction.…”
Section: Introductionmentioning
confidence: 99%
“…Several markerless lung tumor tracking methods have been proposed using MV electronic portal imaging devices (EPID) (Richter et al , 2010; Rottmann et al , 2013; Bryant et al , 2014; Serpa et al , 2014) or kV imaging systems (Hugo et al , 2010; Lewis et al , 2010; Gendrin et al , 2012; Yang et al , 2012; van Sornsen de Koste et al , 2015). MV EPID based methods are limited by the treatment field size and poor contrast.…”
Section: Introductionmentioning
confidence: 99%
“…Due to low MV contrast, also detection of (moving) fiducial gold markers with a diameter smaller than 0.08 cm was problematic. 10 Based on a series of studies dealing with fiducial marker and marker-less detection during EPID fluoroscopy, [11][12][13][14] it can be concluded that most clinical applications of EPID fluoroscopy are conducted with frame rates between 2 and 12.8 Hz. For tumors with a velocity component of up to 4.0 cm/s [with a maximum velocity of 9.6 cm/s (Ref.…”
Section: Introductionmentioning
confidence: 99%